2005
DOI: 10.1074/jbc.m503673200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting of Protein Phosphatase-1 by HIV-1 Tat Protein

Abstract: Transcription of human immunodeficiency virus (HIV)-1 genesis activated by HIV-1 Tat protein, which induces phosphorylation of the C-terminal domain of RNA polymerase-II by CDK9/cyclin T1. We previously showed that Tat-induced HIV-1 transcription is regulated by protein phosphatase-1 (PP1). In the present study we demonstrate that Tat interacts with PP1 and that disruption of this interaction prevents induction of HIV-1 transcription. We show that PP1 interacts with Tat in part through the binding of Val 36 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 44 publications
5
81
0
Order By: Relevance
“…We previously hypothesized that during HIV-1 infection, the viral Tat protein serves as a PP1-targeting subunit. Here, we found that the expression of cdNIPP1 disrupts the association of Tat with PP1; this disruption could be a mechanism for inhibiting HIV-1 transcription, similar to the previously reported HIV-1 inhibitory effect of Tat mutations that prevented binding of Tat to PP1 (24). Accordingly, we observed the inhibition of HIV-1 transcription by a short peptide containing the RVTF sequence, although the effect was relatively small likely due to the problem with cell permeability and inefficient delivery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We previously hypothesized that during HIV-1 infection, the viral Tat protein serves as a PP1-targeting subunit. Here, we found that the expression of cdNIPP1 disrupts the association of Tat with PP1; this disruption could be a mechanism for inhibiting HIV-1 transcription, similar to the previously reported HIV-1 inhibitory effect of Tat mutations that prevented binding of Tat to PP1 (24). Accordingly, we observed the inhibition of HIV-1 transcription by a short peptide containing the RVTF sequence, although the effect was relatively small likely due to the problem with cell permeability and inefficient delivery.…”
Section: Discussionsupporting
confidence: 89%
“…One of the major nuclear regulators of PP1 is NIPP1 (nuclear inhibitor of PP1), which inhibits the dephosphorylation of a wide range of PP1 substrates (22,23). Tat-mediated HIV-1 transcription is blocked by the expression of NIPP1, and the inhibition is reversed by the co-expression of PP1␥ (21 motif and potentially functions as a PP1 regulatory subunit (24). Mutation of residues in the PP1-binding motif (V36A and F38A) prevents Tat from inducing HIV-1 transcription and the translocation of PP1 to the nucleus (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein phosphatases are recruited to genes as part of complexes containing histone-modifying or chromatin-remodeling activities, 70 for example HDAC complexes, 71,72 and by transcription factors such as REST/ NRSF 73 or the HIV-1 Tat protein. 74 We found that both protein phosphatases PP1 and PP2A interact with the transcription factor Sp3. We have demonstrated that PP1 is recruited to the p21 CIP1 promoter and other Sp3-repressed genes in a Sp3-dependent manner.…”
Section: Acknowledgmentsmentioning
confidence: 77%
“…We also compared ARC with poly(I-C), that inhibits protein translation by activating PKR and inducing the phosphorylation of eukaryotic initiation factor 2 a (Nekhai et al, 2000). We observed similar inhibition of protein translation with 100 mM ARC and with (Ammosova et al, 2005) were expressed in Escherichia coli and purified on an Aquapore RP-300 column (Applied Biosystems, Foster City, CA, USA) by reversed-phase chromatography as we described previously (Deng et al, 2002). CEM-GFP cells were treated in a 96-well plate with purified recombinant Tat added at 0.8 mg per 300 000 cells per well along with 100 mM chloroquine (Ammosova et al, 2003), and with the indicated concentrations of ARC.…”
mentioning
confidence: 68%